Spirit matters : occult beliefs, alternative religions, and the crisis of faith in Victorian Britain - Franklin, J. Jeffrey (Cornell University Press, 2018)
"Spirit Matters explores the heterodox and unorthodox religions and spiritualities that arose in Victorian Britain as a result of the faltering of Christian faith in the face of modernity, the rise of the truth-telling authority of science, and the first full exposure of the West to non-Christian religions. J. Jeffrey Franklin investigates the diversity of ways that spiritual seekers struggled to maintain faith or to create new faiths by reconciling elements of the Judeo-Christian heritage with Spiritualism, Buddhism, occultism, and scientific naturalism. Spirit Matters covers a range of scenarios from the Victorian hearth and the state-Church altar to the frontiers of empire in Buddhist countries and Egyptian crypts. Franklin reveals how this diversity of elements provided the materials for the formation of new hybrid religions and the emergence in the 20th century of New Age spiritualities." -- Publisher's description